Use of Arabic Language Learning Media at Madani Islamic Boarding School Payakumbuh Integrated Islamic Junior High School - Rifki Zaitul Ikhlas; Abdul Muntaqim Al Anshory; Nur Hasaniyah (Yayasan Adra Karima Hubbi, 2024)
The use of learning media is important in improving the effectiveness of Arabic language learning at SMP-IT Madani Islamic Boarding School Payakumbuh. In today's digital era, the integration of technology in education is becoming increasingly relevant to create a more interactive and engaging learning environment for students. The purpose of this study is to find out the process of using technological media in improving students' understanding of Arabic, as well as to identify the challenges faced in its application. The research method used was descriptive qualitative with a case study approach. Data were collected through direct observation, in-depth interviews with teachers and students, and analysis of related documents. This approach enabled the researcher to gain an in-depth understanding of the teachers' and students' experiences and perceptions of the use of technological media in learning. The result of this study is that the use of technological media has provided various benefits in Arabic language learning at SMP IT Madani Islamic Boarding School. Teachers use blended learning approach and utilise learning videos from YouTube to teach various Arabic language skills, especially speaking ability and vocabulary memorisation. The conclusion of this study is that technological media has great potential to improve the quality of Arabic language learning at SMP-IT Madani Islamic Boarding School Payakumbuh. To optimise its benefits, it is necessary to increase access to technology for all students, continuous training for teachers, and development of learning content in accordance with the curriculum. With these steps, it is hoped that the Arabic learning process can become more effective and enjoyable for students.